Implementasi Sistem Informasi Manajemen Penerimaan Peserta Didik Baru (SIM-PPDB) Berbasis Microsite di SMP Negeri 3 Purwodadi Tahun 2023 - Auliahaq, Dafa Agta; Rejeki , Rara Sri Artati; Priyadi, Priyadi; Priyadi , Agus; Santoso, Lukman (MEANS (Media Informasi Analisa dan Sistem), 2024)
The Microsite-Based New Student Admissions Management Information System (Sim-Ppdb) at SMP Negeri 3 Purwodadi in 2023 has not yet used a web-based information system. This information system is an information system that is used to help manage the implementation of PPDB activities. So that the management of activities can be controlled and recorded properly.In developing the PPDB management information system at SMP Negeri 3 Purwodadi using the waterfall method, the field study method and literature study were used for data collection. This information system is created using the PHP programming language and MySQL database server. The test method uses black box and usability testing. The results of this study are a microsite-based information system that can make it easier for users, both prospective students, prospective parents and school committees, to access the microsite so that it can be controlled properly. The results of testing the developed software obtained a functionality value of 1 (Good), testing the usability aspect obtained a result with a percentage of 94.66% (Very Eligible).